Development of a multi-axial mechatronic training and testing device for alpine ski racers - Raschner, C.; Patterson, C.; Barth, M.; Barth, A. (Science and Skiing V. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2012)
INTRODUCTION: Strength and power are very important in ski racing so high quality training and testing of these qualities is imperative. High performance athletes in seasonal sports must have conditioning programs which include sport-specific technical aspects. Mechatronic systems utilizing mechanical, electrical, electronic and software components are commonplace in industry. Published documentation of robotic applications in sport science is rare, with the exception of isokinetic devices (Haddadina et al., 2009). The aim of this project was to develop a multi-axial mechatronic-based leg strength training and testing device.